2020
DOI: 10.3389/feart.2020.00065
|View full text |Cite
|
Sign up to set email alerts
|

Englacial Warming Indicates Deep Crevassing in Bowdoin Glacier, Greenland

Abstract: All around the margins of the Greenland Ice Sheet, marine-terminating glaciers have recently thinned and accelerated. The reduced basal friction has yielded increased flow velocity, while the rate of longitudinal stretching has been limited by ice viscosity, which itself critically depends on temperature. However, ice temperature has rarely been measured on such fast-flowing and heavily crevassed glaciers. Here, we present a 3-year record of englacial temperatures obtained 2 (in 2014) to 1 km (in 2017) from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 50 publications
0
22
1
Order By: Relevance
“…The energy input and sink required to sustain the anomaly can be used to estimate the deformation rate. Strain heating, Q s , is expressed as , where τ is the deviatoric stress tensor and is the strain rate tensor ( 10 , 16 ). Stress and strain are related via ( 44 , 45 ), where τ e is the effective stress and , and A is the creep parameter, which we take as 7.7 × 10 −25 s −1 Pa −3 following aggregate values in Cuffey and Paterson [( 16 ), table 3.3] with the range 6.7 × 10 −25 to 8.7 × 10 −25 s −1 Pa −3 , used to test parameter sensitivity and the flow exponent n ≈ 3.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The energy input and sink required to sustain the anomaly can be used to estimate the deformation rate. Strain heating, Q s , is expressed as , where τ is the deviatoric stress tensor and is the strain rate tensor ( 10 , 16 ). Stress and strain are related via ( 44 , 45 ), where τ e is the effective stress and , and A is the creep parameter, which we take as 7.7 × 10 −25 s −1 Pa −3 following aggregate values in Cuffey and Paterson [( 16 ), table 3.3] with the range 6.7 × 10 −25 to 8.7 × 10 −25 s −1 Pa −3 , used to test parameter sensitivity and the flow exponent n ≈ 3.…”
Section: Methodsmentioning
confidence: 99%
“…The energy input and sink required to sustain the anomaly can be used to estimate the deformation rate. Strain heating, Q s , is expressed as Q s = tr( ̇ ) , where  is the deviatoric stress tensor and ̇ is the strain rate tensor (10,16). Stress and strain are related via ̇ = A  e n−1  (44,45), where  e is the effective stress and τ e 2 = 1 _ 2 tr(  2 ) , and A is the creep parameter, which we take as 7.…”
Section: Anomaly-208 Heat Transfer and Deformationmentioning
confidence: 99%
See 1 more Smart Citation
“…Moulins have been shown to migrate horizontally with depth (Holmund, 1988), which could possibly avoid this objection; however, numerous moulins would be needed to generate the cooling we observe in multiple boreholes. In the ablation zone surrounding Issunguata Sermia, active moulins have a mean density of 0.1 per square kilometer (Smith et al, 2015), and Catania and Neumann (2010) found relict moulins to be spaced ∼ 1 km apart, which suggests that it is unlikely that multiple moulins have thermally altered the instrumented block of ice with a surface area of ∼ 0.125 km 2 .…”
Section: Thermal Decay From Basal Crevassesmentioning
confidence: 99%
“…1a). Field campaigns on Bowdoin Glacier were repeated in the summers of 2013-2017 and 2019 in a collaboration between Hokkaido University, ETH Zurich and University of Florence (Podolskiy et al, 2017;Seguinot et al, 2020).…”
mentioning
confidence: 99%